Carbon storage of seagrass ecosystems may experience tipping points in response to anthropogenic stress - a modeling perspective - Dakos, Vasilis; Le Vilain, Antoine; Thebault, Elisa; Alcoverro, Teresa; Boada, Jordi; Infantes, Eduardo; Krause-Jensen, Dorte; Marbà, Núria; Serrano, Oscar; Vizzini, Salvatrice; Apostolaki, Eugenia T. (Frontiers in Complex Systems, 2025)
Coastal Blue Carbon ecosystems like seagrass meadows are foundation habitats with a capacity to sequester and store organic carbon in their sediments, and their protection and restoration may thereby support climate change mitigation while also supporting biodiversity and many other ecosystem functions. However, seagrass ecosystems are being lost due to human activities, disease and, in some regions, climate change, which may trigger the release of stored carbon into the atmosphere. Yet, we do not fully understand how global change-induced seagrass loss influences sedimentary carbon dynamics. What is even less clear is whether seagrass loss may also result in tipping points, i.e., abrupt and difficult-to-reverse shifts, in carbon flux dynamics turning seagrass ecosystems from net carbon sinks to net carbon sources. Here, we propose that conceptual mechanistic models of coupled ecological and biogeochemical dynamics can help to study the effects of major stressors on seagrass meadows and associated carbon fluxes. We then illustrate one case of such a conceptual model that focuses on anthropogenic induced mortality by physical stress as an example. Our perspective highlights how a modeling approach for understanding the response of carbon fluxes in seagrass ecosystems to global change stressors may be useful in informing coastal seagrass management towards climate change mitigation actions.